Digital genres and english language teaching: a proposal for learning by Design with Tik Tok (Research, Society and Development, 2022)
The present work aims to promote an analysis of the use of the Tik Tok application in reading and writing activities in English, in a multimodal perspective, through a didactic proposal of learning by design, using the digital video-minute genre. As a theoretical framework, I use the concepts of digital technologies (Castells, 2003; Monte-Mor, 2012; Pretto, 2013), among others. Digital genres and multiliteracies receive contributions from (Cope & Kalantzis, 2000; 2015), between others. In terms of methodology, it is a qualitative research, of an exploratory nature, with a bibliographic review and a pedagogical proposal of practical application, providing subsidies for deepening the theme in future research. At the end of the study, I highlight the importance of the English language teacher to think his teaching practice aligned with real needs and contextualized with the transformations of communicative spaces and social relations, due to the increasingly constant integration of digital technologies in the daily life of humanity.